Impact of empagliflozin in heart failure with reduced ejection fraction in patients with ischemic versus nonischemic cause - Khan, Muhammad Shahzeb; Butler, Javed; Anker, Stefan D.; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Januzzi, James L.; Piña, Ileana L.; Böhm, Michael; Ponikowski, Piotr; Verma, Subodh; Brückmann, Martina; et al. (Journal of the American Heart Association, 2023)
Background - Outcomes and treatment effects of therapy may vary according to the cause of heart failure (HF). - Methods and Results - In this post hoc analysis of the EMPEROR‐Reduced (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction) trial, the effect of empagliflozin on cardiovascular and renal outcomes was assessed according to the cause of HF. The cause of HF was investigator reported and stratified as ischemic or nonischemic. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% CIs. Of the 3730 patients enrolled, 1929 (51.7%) had ischemic cause. In the placebo arm, patients with ischemic cause of HF did not have a significantly higher risk of cardiovascular mortality (HR, 1.21 [95% CI, 0.90-1.63]) and hospitalization for HF (HR, 0.90 [95% CI, 0.72-1.12]) compared with nonischemic cause. Empagliflozin compared with placebo significantly reduced the risk of cardiovascular death or hospitalization for HF in patients with ischemic and nonischemic cause (HR, 0.82 [95% CI, 0.68-0.99] for ischemic and HR, 0.67 [95% CI, 0.55-0.82] for nonischemic cause; P interaction=0.15). The benefit of empagliflozin on HF hospitalization, the renal composite end point, estimated glomerular filtration slope changes, and health status scores were also consistent in both groups without treatment by cause modification. - Conclusions - Empagliflozin offers cardiovascular and renal benefits in patients with heart failure with reduced ejection fraction regardless of the cause of HF. - Registration - URL: https://www.clinicaltrials.gov; Unique identifier: NCT03057977.
Onlin veröffentlicht: 24. Dezember 2022
Gesehen am 07.08.2024